Becoming-Animal: Negotiating Insider/Outsider Politics in Leah Chishugi’s A Long Way from Paradise - Amimo, Maureen (WritingThreeSixty, 2018)
Mobility practices in the postmodern world have enhanced free circulation of people, objects, ideas, and services. In the same vein, surveillance and boundary policing has also emerged. Narratives of forced flight exemplify this surveillance in detail. In this paper I explore the complexities of becoming-animal inherent in political crises that exploit insider/outsider trajectories. I employ Deleuze and Guattari’s concept of becoming-animal to tease out the nodes of becoming-animal in Leah Chishugi’s A Long Walk from Paradise. To do this I focus on how the image of the ‘inyenzi’ (cockroach) is conceptualised by the different entities within the ‘war machine’ of Rwanda genocide to validate insider/outsider surveillance and status. This study furthers the conception of becoming-animal by teasing out the affective connections emergent from becoming-cockroach and what this form of becoming allows the narrator to negotiate. This paper concludes that while becoming-animal is a tactic of extermination employed by the war machine, embracing-animal allows for a troubling of the insider/outsider relations at the centre of such logic as well as understanding of human and animal relations.